The Neurocircuitry Underlying Additive Effects of Safety Instruction on Extinction Learning - Javanbakht, Arash; Grasser, Lana Ruvolo; Madaboosi, Shantanu; Chowdury, Asadur; Liberzon, Israel; Diwadkar, Vaibhav A. (Frontiers in Behavioral Neuroscience, 2021)
Extinction learning is the dominant laboratory model for exposure therapy, a treatment involving both experience of safety near the feared object, and safety instructions relayed by a therapist. While the experiential aspect of extinction learning is well researched, less is known about instructed extinction learning and its neurocircuitry. Here, in 14 healthy participants we examined the neural correlates of, and the network interactions evoked by instructed extinction learning. Following fear conditioning to two CS+ stimuli, participants were instructed about the absence of the aversive unconditioned stimulus (US) for one of the CS+s (instructed CS; CS+I) but not the second CS+ (uninstructed CS+; CS+U). Early during extinction learning, greater activation was observed for the CS+I>CS+U contrast in regions including the vmPFC, dmPFC, vlPFC, and right parahippocampus. Subsequently, psychophysiological interaction (PPI) was applied to investigate functional connectivity of a seed in the vmPFC. This analyses revealed significant modulation of the dmPFC, parahippocampus, amygdala, and insula. Our findings suggest that the addition of cognitive instruction yields greater activation of emotion regulation and reappraisal networks during extinction learning. This work is a step in advancing laboratory paradigms that more accurately model exposure therapy and identifies regions which may be potential targets for neuromodulation to enhance psychotherapy effects.